2000
DOI: 10.1108/02656710010315238
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of quality management practices in Shanghai and Norwegian manufacturing companies

Abstract: Records the research that investigates the differences in quality management between Shanghai and Norwegian manufacturing companies. The research is based on a survey supported by the Norwegian Association for Quality Management (NFK) and the Shanghai Association for Quality Control (SAQC). The research reveals major differences between the two parties. Compared with their Norwegian counterparts, Shanghai companies place greater emphasis on quality control and statistical methods while neglecting customer sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 9 publications
2
58
0
3
Order By: Relevance
“…Without benchmarking, organisations do not know their relative performance and they probably fail to design processes more effectively (Rao, Solis, and Raghunathan 1999). Sun (2000) finds a significant correlation between benchmarking and business results. The authors suggest that practitioners use the measurement instrument by Das, Paul, and Swierczek (2008).…”
Section: Benchmarkingmentioning
confidence: 99%
“…Without benchmarking, organisations do not know their relative performance and they probably fail to design processes more effectively (Rao, Solis, and Raghunathan 1999). Sun (2000) finds a significant correlation between benchmarking and business results. The authors suggest that practitioners use the measurement instrument by Das, Paul, and Swierczek (2008).…”
Section: Benchmarkingmentioning
confidence: 99%
“…This relational culture promotes long-term orientation and contributes to the development of lasting cooperation between the companies. The focus is on customer satisfaction and quality assurance, rather than just on costs [17].…”
Section: Discussion: Cultural Characteristics and Their Effect Onmentioning
confidence: 99%
“…The ability to deliver in accordance to specifications and schedule has also been identified as one of the main reasons for winning contracts [13]. Sun [17] provides further evidence of differences in quality between Norway and low-cost countries. His study showed that Chinese companies tend to pursue a low quality and low price strategy, and companies trying to produce products to Norwegian standards end up with prices just as high as in Norway.…”
Section: The Case: Norwegian North-western Møre Maritime Clustermentioning
confidence: 99%
“…The impact of employee support in achieving quality goals has already been praised by many authors (Ahire et al, 1996;Black and Porter, 1996;Blackburn and Rosen, 1993;Clemmer, 1990;Creech, 1994;Evans and Lindsay, 2002;Kanji and Asher, 1993;Oakland, 2000;Sun, 2000;Thiagarajan and Zairi, 1997). Middle management and shop floor employees need to be involved in the organisational process as major internal stakeholders.…”
Section: Employee Involvement and Participationmentioning
confidence: 99%